2020
DOI: 10.1002/edm2.118
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coenzyme Q10 on metabolic and cardiovascular disease profiles in diabetic patients: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Aims: Coenzyme Q 10 (CoQ10) is well known for its beneficial effects in cardiovascular disease (CVD); however, reported evidence has not been precisely synthesized to better inform on its impact in protecting against cardiovascular-related complications in diabetic patients. Materials and Methodology:The current meta-analysis included randomized controlled trials published in the past 5 years reporting on the effect of CoQ10 on metabolic and CVD-related risk profiles in individuals with diabetes or metabolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Endothelial dysfunction, a condition that contributes to the pathogenesis of vascular disease in T2DM, is considered a reliable marker of subclinical atherosclerotic cardiovascular disease, as it appears before the development of atherosclerotic lesions or the occurrence of clinical events. Endothelial dysfunction is also described as being involved in the deterioration of cardiac function, especially in conditions of metabolic disease [ 40 ]. Several studies have demonstrated the effect of CoQ 10 supplementation on endothelial function in patients with type 2 diabetes mellitus, CAD or in elderly people [ 41 , 42 , 43 ], showing that flow-mediated dilation (FMD) or nitroglycerin-mediated dilation (NMD) and extracellular superoxide dismutase activity increased in most of the subjects treated with CoQ 10 , which could be attributed to its antioxidant and anti-inflammatory activity [ 36 , 43 , 44 ].…”
Section: Coq 10 and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Endothelial dysfunction, a condition that contributes to the pathogenesis of vascular disease in T2DM, is considered a reliable marker of subclinical atherosclerotic cardiovascular disease, as it appears before the development of atherosclerotic lesions or the occurrence of clinical events. Endothelial dysfunction is also described as being involved in the deterioration of cardiac function, especially in conditions of metabolic disease [ 40 ]. Several studies have demonstrated the effect of CoQ 10 supplementation on endothelial function in patients with type 2 diabetes mellitus, CAD or in elderly people [ 41 , 42 , 43 ], showing that flow-mediated dilation (FMD) or nitroglycerin-mediated dilation (NMD) and extracellular superoxide dismutase activity increased in most of the subjects treated with CoQ 10 , which could be attributed to its antioxidant and anti-inflammatory activity [ 36 , 43 , 44 ].…”
Section: Coq 10 and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Supplementation with 5 µM CoQ is an efficient way of protecting endothelial cells in vitro against damage caused by hyperglycemia and angiotensin II [10,12]. Indeed, CoQ supplementation has substantiated clinical benefits in the prevention and treatment of hypertension and T2DM [28,40,79,81,82], and recently it has been reported that the beneficial effects of CoQ in lowering the CVD risk are associated with improving endothelial health [83]. The in vitro results presented herein regarding the effects of plasma from patients receiving Ub oral supplementation for 1 year on endothelial are limited only to the analysis of cell necrosis, and they are consistent with these data.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent systematic review and meta-analysis of 12 randomized controlled trials enrolling a total of 650 patients examined the effect of CoQ10 on metabolic and CVD-related risk profiles in individuals with diabetes or metabolic syndrome. This study concluded that CoQ10 supplementation showed greater potential to lower CVD risk in diabetic patients by lowering total cholesterol and LDL levels when compared to those on placebo, which was associated with an improvement of endothelial health [ 41 ].…”
Section: Coq10 Endothelial Dysfunction and Hypertensionmentioning
confidence: 99%